Basicity of isostructural porous ionic crystals composed of Nb/Ta-substituted Keggin-type polyoxotungstates. Issue 21 (27th April 2022) - Weng, Zhewei; Ogiwara, Naoki; Yokogawa, Daisuke; Kitao, Takashi; Kikukawa, Yuji; Uchida, Sayaka
Abstract : Three isostructural porous ionic crystals (PICs) based on Keggin-type POMs with different compositions but equal negative charge ([BW12 O40 ] 5−, [SiW11 NbO40 ] 5−, and [SiW11 TaO40 ] 5− ) are synthesized. Abstract : Three isostructural porous ionic crystals (PICs) based on Keggin-type POMs with different compositions but equal negative charge ([BW12 O40 ] 5− (BW12 ), [SiW11 NbO40 ] 5− (SiW11 Nb ), and [SiW11 TaO40 ] 5− (SiW11 Ta )) are synthesized. Experimental and theoretical characterizations of the three PICs (1_BW12, 1_SiW11 Nb, and 1_SiW11 Ta ) show that the substitution of Nb/Ta for W in the POMs enhances the basicity of PICs, which increases in the order of 1_BW12 < 1_SiW11 Nb < 1_SiW11 Ta . These findings clearly show that the increase in basicity is due not only to the increase in negative charge of the POM molecule as is often explained, but also to the character of the substituted element itself.